Productivity enhancement and biofortification of maize (Zea mays)- wheat (Triticum aestivum) cropping system through integrated potassium management - KUMAR, SANJEEV; DHAR, SHIVA; MEENA, RANG LAL; OM, HARI (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during the kharif and rabi seasons of 2010-11 and 2011-12 at Indian Agriculture Research Institute, New Delhi to find out the performance of maize (Zea mays L.) - wheat (Triticum aestvum L.) cropping system with integrated potassium management through muriate of potash and farmyard manure. The experiment was laid out in randomized block design consisted of ten treatments and replicated thrice. Results revealed that all the treatment with potassium irrespective of sources significantly increased grain yield and nutrient concentration in grain of maize and wheat. The application of 60 kg K through muriate of potash + 30 kg K through farmyard manure resulted into highest grain yield of maize (4.44 and 5.42 tonnes/ ha) and wheat (5.39 and 5.49 tonnes/ ha). All treatment applied with farmyard manure shows higher macro – micro nutrient concentration in grain over control. The application of 60 kg potassium supplemented as 30 kg K through MOP and 30 kg K through farmyard manure in maize and application of 60 kg K through MOP alone in wheat resulted into highest system productivity (7.82 and 8.81 tonnes/ha).